KESIAPAN GURU MENGIMPLEMENTASIKAN KURIKULUM 2013 DI SMA NEGERI 1 PANTAI CERMIN - Surianto, Putra - (Pendidikan Sosiologi, 2014)
Education will not be able to run without the curriculum, while the shooting went curriculum should always be developed in accordance with the times. The implementation of the curriculum in 2013 in SMA N 1 Pantai Cermin real mirrors are not yet ready because of SMA N 1 Pantai Cermin is not a former school RSBI and not accredited and facilities are inadequate and delay the training of teachers. This study aimed to describe the readiness of sociology teachers implement the curriculum in 2013 in the learning process of Sociology at SMA N 1 Pantai Cermin, Solok regency. Determination of informants is the porposive sampling techniques. Techniques of data collection is done by tracking documents, observations and interviews. The unit is an individual data analysis and data analysis using interactive model proposed by Milles and Huberman stages of data collection, data reduction, data presentation, and drawing kesimpulan.Berdasarkan results of research conducted, it can be concluded that (1). Readiness teachers in planning that teachers are able to create lesson plans teacher lesson plans curriculum in 2013 and is in accordance with the scope Permendikbud 2013 81A (2). Readiness of teachers in the implementation of learning that teachers already menerapkankan scientific approach in the process of learning is done in class. (3). Readiness teachers in an authentic assessment that teachers have not applied all manner of authentic assessment to students both in assessing the attitudes, skills and knowledge. Thus it can be concluded that sociology teachers not yet fully ready to implement Curriculum 2013.